2016
DOI: 10.1002/gps.4450
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antidepressant use in community‐dwelling persons with and without Alzheimer's disease: 13‐year follow‐up

Abstract: The incidence of antidepressant use was higher in persons with AD than in comparison persons, and it was not explained by history of hospital-treated psychiatric disorders. Widespread use of antidepressants in persons with AD is concerning as their efficacy is controversial and their use is associated with adverse events. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…In addition, due to the long exposure assessment, we were able to use a 5‐year time lag between exposure and outcome, which is longer than in main analyses of most of the previous studies and accounts at least partially for the reverse causality. The 5‐year time lag is justified by our previous studies in the same population, showing that a steep increase in the use of antidepressants and antipsychotics occurs in this time window.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, due to the long exposure assessment, we were able to use a 5‐year time lag between exposure and outcome, which is longer than in main analyses of most of the previous studies and accounts at least partially for the reverse causality. The 5‐year time lag is justified by our previous studies in the same population, showing that a steep increase in the use of antidepressants and antipsychotics occurs in this time window.…”
Section: Discussionmentioning
confidence: 96%
“…Antidepressant drug use is more prevalent in older adults than in the general population, with the highest rates seen in institutionalized older people [98,99]. Antidepressant use is more common in persons with AD compared with those without dementia [100]. The incidence of antidepressant use in older adult populations varies by country with a range of 4.7-18.6% [101].…”
Section: Antidepressantsmentioning
confidence: 99%
“…[11][12][13] Results from studies of the elderly investigating the underuse and overuse of antidepressants are controversial. [16][17][18] A recent review of seniors aged 55 years and older found antidepressant use in only 20% to 45% of persons with depression. 9,14,15 However, it was also reported that antidepressants are often used without justification and that antidepressant prescriptions may be influenced by social factors such as loneliness or by the presence of somatic comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…9,14,15 However, it was also reported that antidepressants are often used without justification and that antidepressant prescriptions may be influenced by social factors such as loneliness or by the presence of somatic comorbidities. [16][17][18] A recent review of seniors aged 55 years and older found antidepressant use in only 20% to 45% of persons with depression. 19 A cross-sectional US-American study pointed out that only 45.6% of older patients with depression received any treatmentmostly pharmacotherapy-whereas psychotherapy was present in only 8.4%.…”
Section: Introductionmentioning
confidence: 99%